2000
DOI: 10.1016/s0194-5998(00)70055-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Suspension Suture with Repose Bone Screw for Obstructive Sleep Apnea

Abstract: A pharyngeal suspension suture changes subjective outcomes. Improvement is incomplete. The procedure is nonexcisional, but significant complications may occur. Further evaluation is required to demonstrate effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 19 publications
0
31
0
2
Order By: Relevance
“…The reviewed studies reported on significant improvements in snoring and daytime sleepiness. An improvement in the Functional Outcomes of Sleep Questionnaire score was reported in the study by WOODSON et al [302] on tongue suspension.…”
Section: Discussionmentioning
confidence: 70%
“…The reviewed studies reported on significant improvements in snoring and daytime sleepiness. An improvement in the Functional Outcomes of Sleep Questionnaire score was reported in the study by WOODSON et al [302] on tongue suspension.…”
Section: Discussionmentioning
confidence: 70%
“…Adjustability may be one of the reasons why we achieved somewhat better results than in the Repose system. 16 The success rate of the Advance System II was 38.9%, which is lower than established treatment modalities such as CPAP treatment, with efficacy of 90%, 5 or UPPP with 50% efficacy. 6 …”
Section: Discussionmentioning
confidence: 86%
“…This feasibility study achieved a 50% drop in AHI to a score below 15 at 6 months in 39% of the study subjects. Woodson et al 16 reported limited objective improvement after tongue suspension (Repose). The study showed that technical problems can be solved but also stressed the importance of deep knowledge of tongue forces for avoiding additional technical problems.…”
Section: Discussionmentioning
confidence: 99%
“…Die Studien von Woodson[252,253] beinhalten zum Teil identische Patientendaten, weshalb für die Berechnung der Durchschnittswerte nur die jüngere Publikation benutzt wurde. Die Studien von Woodson[252,253] beinhalten zum Teil identische Patientendaten, weshalb für die Berechnung der Durchschnittswerte nur die jüngere Publikation benutzt wurde.…”
unclassified